Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5604/12321966.1219198
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of menopausal symptoms among female inhabitants of East European countries

Abstract: The objective of the study was analysis of the occurrence and intensity of menopausal symptoms in postmenopausal women from Poland, Belarus, Ukraine, Czech Republic, Slovakia and Poland. The study was conducted during the period 2014-2015 among postmenopausal women living in the areas of Poland, Belarus, Ukraine, Czech Republic and Slovakia. The degree of menopausal complaints was assessed using the Kupperman Menopausal Index and Greene Climacteric Scale. The respondents were additionally asked about age, educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…In the study, it was observed that the women with a lower educational level had higher psychological complaints and lower urogenital complaints. Similar to the results of the present study, some studies revealed that women with a lower educational level had more psychological problems . Similarly, in Makara‐Studzińska's study, women with the most severe menopausal symptoms had the worst educational level .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the study, it was observed that the women with a lower educational level had higher psychological complaints and lower urogenital complaints. Similar to the results of the present study, some studies revealed that women with a lower educational level had more psychological problems . Similarly, in Makara‐Studzińska's study, women with the most severe menopausal symptoms had the worst educational level .…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the results of the present study, some studies revealed that women with a lower educational level had more psychological problems. [19][20][21] Similarly, in Makara-Studzińska's study, women with the most severe menopausal symptoms had the worst educational level. 22 Unlike the results of the present study, a study suggested that there was no significant correlation between the educational level and psychological complaints of women.…”
Section: Discussionmentioning
confidence: 90%
“…Demographic data have shown that every year, 25 million women worldwide experience the menopause. This will result in 1.2 billion postmenopausal women worldwide by 2030 [2]. The menopause in white Caucasian women occurs on average at age 51 (with ethnic and regional variations) [3], while in Asian countries, the mean age of onset of the menopause varies, with the mean age of onset in Taiwanese women at 49.3 years as reported in a study in 1997 [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the multiple regression analysis, however, it was found that urban living may potentially influence the subjective experience of VMS as this is manifested in the HFBS score. Most previous studies indicate that women in rural areas experience fewer menopausal symptoms than those living in urban areas [20], but other studies are not in the same line [21]. In general, evidence suggests that residence is an influential factor for menopausal symptoms [22,23].…”
Section: Discussionmentioning
confidence: 97%